2014
DOI: 10.1007/s10994-013-5433-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting concept change in dynamic data streams

Abstract: In this research we present a novel approach to the concept change detection problem. Change detection is a fundamental issue with data stream mining as classification models generated need to be updated when significant changes in the underlying data distribution occur. A number of change detection approaches have been proposed but they all suffer from limitations with respect to one or more key performance factors such as high computational complexity, poor sensitivity to gradual change, or the opposite prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…False positive rate is controlled by adjusting the user parameter significance level of a hypothesis test. Because of multiple passes on data in the current histogram, false positive rate, especially in a noisy environment, is relatively higher than SeqDrift2 .…”
Section: Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…False positive rate is controlled by adjusting the user parameter significance level of a hypothesis test. Because of multiple passes on data in the current histogram, false positive rate, especially in a noisy environment, is relatively higher than SeqDrift2 .…”
Section: Related Researchmentioning
confidence: 99%
“…In contrast, SeqDrift2 was stable at these points in the stream. In , it was shown that ADWIN's false positive rate was higher than that of SeqDrift2 and false positives signaled by ADWIN can cause existing spectra that are performing well to be switched to a new spectrum which under performs. This problem was particularly acute at low‐memory setting of pool Size 1.…”
Section: Empirical Case Studymentioning
confidence: 99%
See 3 more Smart Citations